Epidemiological characteristics of 1,806 patients with traumatic spinal cord injury: A retrospective study - Wang, Zhihua; Zhou, Wu; Li, Meihua (Frontiers in Surgery, 2023)
Background: Traumatic spinal cord injury (TSCI) is a type of highly disabling central nervous system trauma. In this study, we investigated the epidemiological characteristics of 1,806 TSCI patients and compared the characteristics of patients with traumatic cervical spinal cord injury (TCSCI) caused by cervical fracture/dislocation and disc herniation/bulging. Methods: We retrospectively reviewed the hospital records of 1,806 TSCI patients. The detailed information included gender, marital status, occupation, age, neurological level of injury, etiology, American Spinal Injury Association (ASIA) grade, combined injuries, complications, treatment, the interval between admission and surgery, intubation/tracheostomy requirement, and the length of hospital stay. Results: Cervical spinal cord injury (CSCI) was the most common injury. Compared to non-CSCI cases, patients with TCSCI were older, and more likely to suffer from tetraplegia and require intubation/tracheostomy, but had fewer other injuries or complications and a shorter length of hospital stay. Compared to patients with cervical fracture/dislocation, those with TCSCI caused by disc herniation/bulging were older and more likely to suffer from paraplegia, but required intubation/tracheostomy less frequently, exhibited fewer other injuries and complications, and required shorter hospitalization. Conclusions: Men, married individuals, manual laborers, and individuals aged 31–75 years had the highest risk of TSCI. Patients with TCSCI tended to have a shorter length of hospital stay than patients with non-CSCI. More attention should be paid to the other injuries and complications of non-CSCI patients, which may increase the length of hospital stay and delay rehabilitation. Compared to patients with cervical disc herniation, the patients with fracture/dislocation tended to be younger, but prognosis was severely compromised by tetraplegia, a greater need for intubation/tracheostomy, additional injuries, and complications.